Spatial congruence between biodiversity and ecosystem services in a forest landscape in southern Chile: basis for conservation planning - Rodríguez-Echeverry, James; Echeverría, Cristian; Oyarzún, Carlos; Morales, Luis (BOSQUE, 2017)
There is a need for a better understanding on how biodiversity and ecosystem services are spatially related and assess to what extent the conservation of biodiversity will ensure the provision of services. In the Río Cruces watershed (Chile) the spatial congruence between biodiversity and water supply, erosion control and soil accumulation services was assessed using spatially explicit models, geographically weighted regression and overlap analyses. Biodiversity registered a positive spatial relationship with the three ecosystem services. The local R2 value explained up to 95 %, 68 % and 37 % of the variance for soil accumulation, water supply and erosion control, respectively. High spatial congruence (> 67 %) was registered between biodiversity and ecosystem services hotspots. Our study recommends that decision makers develop plans and share efforts for conservation of biodiversity and ecosystem services in 43 subwatersheds, which are 16.4 % of the subwatersheds studied. We suggest that these efforts must be an integral part of environmental policies that need to be generated by the Chilean government.